State dependent perceptual learning - Scott, Craig (2021)
Visual perception is vitally important for most everyday tasks. Whether reading a book, crossing a busy road or picking up on subtle changes in the facial expression of a friend, we rely on our brains to accurately and rapidly interpret the patterns of light captured by our eyes. Whilst seemingly effortless, these tasks rely upon complex processing, which is refined by practice and experience – via a process termed perceptual learning. Due to the prevalence of perceptual learning it is considered to be a widespread property of visual processing.